Comparison of public health and preventive medicine physician specialty training in six countries: Identifying challenges and opportunities. (1st November 2016) - Peik, Samuel M.; Mohan, Keerthi M.; Baba, Toshiaki; Donadel, Morgane; Labruto, Andrea; Loh, Lawrence C.
Abstract: Rationale : Public health and preventive medicine (PHPM) has been recognized internationally as a physician specialty, but national parallels and differences exist between training contexts. This paper reviews PHPM training and employment in Canada, France, Italy, Japan, the United Kingdom, and the USA. Methods : Information gathered from relevant accreditation bodies and literature searches was used to create descriptive profiles of national training demographics and structure and a narrative outlining trends and challenges facing the specialty. Results : Notable similarities and differences exist between national contexts. Key themes were differences in training strategies and practice scope, specialty stakeholders, certification structure, and funding. Recognition challenges faced the specialty across all six countries. Other challenges included unclear competencies and training strategies and a need for PHPM specialists to highlight their role in combating population health threats. Additional differences existed between comparator countries on the structure of training, funding sources for training programs, availability of training posts, and linkages with other physician specialties. Conclusion : Highlighting these themes is a first step to fostering training collaborations between PHPM specialist physicians to augment transnational action on global public health challenges and also supports PHPM physician educators with innovative solutions from abroad that might address domestic specialty challenges.